"Pre-Ramadan" telemedicine: Effect on fasting experience and glycemic control during ramadan in people with type 1 diabetes. Issue 8 (August 2022) - Alharthi, Sahar; Alrajeh, Areej; Alyusuf, Ebtihal; Alguwaihes, Abdullah M.; Jammah, Anwar; Al-Sofiani, Mohammed E.
Abstract: Objective: People with type 1 diabetes (T1D) are advised to have a "pre-Ramadan" visit to receive the assessment and education needed to safely fast during the holy month of Ramadan. The COVID-19 lockdown has interrupted this standard of care in Muslim-majority countries where telemedicine is not well-established. Here, we examined the impact of virtual"pre-Ramadan" visits, as an alternative option to the traditional (in-person) visits, on fasting experience and glycemic control during Ramadan in people with T1D. Method: 151 individuals with T1D were categorized into 3 groups according to the type of"pre-Ramadan" visit that they attended in 2020: virtual (n = 50), in-person (n = 56), and no visit (n = 45). Number of days fast was broken and CGM metrics were retrospectively compared across the groups. Result: Patients who had a virtual"pre-Ramadan" visit were more likely to use continuous glucose monitors (CGM) than those who had no visit (61.7% and 38.6%, respectively, p < 0.05). Attending a virtual"pre-Ramadan" visit was associated with the least number of days fast was broken compared to those who had no visit (p < 0.01) or in-person visit (p = 0.02). CGM time in range (TIR) during Ramadan was the highest in those who had virtual "Pre-Ramadan" visits compared to those who had no visit or in-person visits (59%, 44%, and 47%, respectively). After adjusting for age, gender, pre-Ramadan A1c, and CGM use, the odds of fasting most days of Ramadan were highest in the virtual group [OR (CI): 9.13 (1.43, 58.22)] followed by the in-person group [3.02 (0.54, 16.68)] compared to the no visit group. Conclusion: Virtual"pre-Ramadan" visits are effective alternative to in-person visits when managing people with T1D who plan to fast during Ramadan.